2018
DOI: 10.1021/acschembio.8b00306
|View full text |Cite
|
Sign up to set email alerts
|

Lawsone, Juglone, and β-Lapachone Derivatives with Enhanced Mitochondrial-Based Toxicity

Abstract: Naphthoquinones are among the most active natural products obtained from plants and microorganisms. Naphthoquinones exert their biological activities through pleiotropic mechanisms that include reactivity against cell nucleophiles, generation of reactive oxygen species (ROS), and inhibition of proteins. Here, we report a mechanistic antiproliferative study performed in the yeast Saccharomyces cerevisiae for several derivatives of three important natural naphthoquinones: lawsone, juglone, and β-lapachone. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…Naphthoquinones have been shown to possess cytotoxic [54,55], antitumor [56] and antimicrobial activities [25,57,58]. Naphthoquinones are among the most active natural products obtained from plants and microorganisms, and they exert their biological activities through pleiotropic mechanisms that include reactivity against cell nucleophiles, generation of ROS, and inhibition of proteins [59].…”
Section: Juglone As An Oxidant: Cytotoxic Potentialmentioning
confidence: 99%
“…Naphthoquinones have been shown to possess cytotoxic [54,55], antitumor [56] and antimicrobial activities [25,57,58]. Naphthoquinones are among the most active natural products obtained from plants and microorganisms, and they exert their biological activities through pleiotropic mechanisms that include reactivity against cell nucleophiles, generation of ROS, and inhibition of proteins [59].…”
Section: Juglone As An Oxidant: Cytotoxic Potentialmentioning
confidence: 99%
“…According to Ramos-Pérez et al [35], the antifungal activity of β-lap is related to its ability to induce ROS production, since a yap1Δ mutant strain was hypersensitive to the quinone at 30 μM. Anaissi-Afonso et al [36] have also observed that βlap and derivatives at 10-100 μM exert their antifungal activity through oxidative stress and mitochondrial disfunction. On the other hand, Menacho-Márquez et al [37] observed that preincubation with dicoumarol did not affect the antifungal toxicity of β-lap, indicating that ROS production is not the mechanism responsible for the toxicity of β-lap against S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that β-lap decreased MMP, indicating an indirect impairment of ATPase activity of Pdr5p, since mitochondrial polarization is essential to ATP production. Previous studies have shown that mitochondria is an important target of β-lap both in fungi [36] and other organisms such as Trypanosoma cruzi [43] and cancer cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Naphthoquinones can act mainly as pro-oxidants, reducing oxygen to reactive oxygen species (ROS) or as electrophiles, forming covalent bonds with tissue nucleophiles [15,16]. The extensively studied naphthoquinones [17][18][19][20][21][22][23][24][25][26][27][28][29][30] showed anticancer activity both in vitro and in vivo via many molecular mechanisms, such as targeting apoptosis, autophagy pathway, cell cycle arrest, anti-angiogenesis pathway, anti-invasion and anti-metastasis pathway. Some of these possess potent antitumor activity by inhibiting the activity of DNA topoisomerase I/II [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%